2000
DOI: 10.1046/j.1460-9568.2000.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of AMPA receptors by cyclothiazide in two types of striatal neurons

Abstract: The modulation of alpha-amino-3-hydroxy-5-methyl-4-isoxazol-propionate (AMPA) receptor-mediated currents by cyclothiazide was investigated in acutely isolated cells from rat striatum with whole-cell patch-clamp recording. Single-cell reverse transcriptase-polymerase chain reaction (RT-PCR) was used to identify medium spiny and giant aspiny neurons and to determine their AMPA receptor subunit composition mostly in separate experiments. After pretreatment with cyclothiazide, kainate-induced AMPA responses were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
46
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 40 publications
9
46
0
Order By: Relevance
“…Consistent with this, single-cell RT-PCR studies have reported that all striatal projection neurons express GluR2, most express GluR1, but few express significant levels of GluR3, and none express GluR4 Stefani et al, 1998;Vorobjev et al, 2000). A ubiquity of GluR2 in striatal projection neurons is consistent with previous immunohistochemical studies using polyclonal antibodies that recognize GluR2/3 or GluR2/3/4c (Tallaksen-Greene and Albin, 1994;Chen et al, 1996;Bernard et al, 1997).…”
Section: Implications For Ampa Receptor Subunit Composition and Functsupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with this, single-cell RT-PCR studies have reported that all striatal projection neurons express GluR2, most express GluR1, but few express significant levels of GluR3, and none express GluR4 Stefani et al, 1998;Vorobjev et al, 2000). A ubiquity of GluR2 in striatal projection neurons is consistent with previous immunohistochemical studies using polyclonal antibodies that recognize GluR2/3 or GluR2/3/4c (Tallaksen-Greene and Albin, 1994;Chen et al, 1996;Bernard et al, 1997).…”
Section: Implications For Ampa Receptor Subunit Composition and Functsupporting
confidence: 87%
“…Moreover, we found that striato-GPe and striatonigral neuron perikarya appear to contain less amounts of GluR2 than do striato-GPi neuron perikarya. The present study further shows that projection neuron perikarya are less rich in GluR1 than GluR2 protein, as also implied by prior ISHH, RT-PCR and immunolabeling studies, and that only 50-70% of striatal projection neuron perikarya contain GluR1 (Bernard et al, 1996(Bernard et al, ,1997Chen et al, 1996Chen et al, ,1998Stefani et al, 1998;Vorobjev et al, 2000). In contrast to the situation for GluR2, we found that striato-GPe perikarya are richer than striato-GPi perikarya in GluR1.…”
Section: Implications For Ampa Receptor Subunit Composition and Functsupporting
confidence: 84%
See 1 more Smart Citation
“…The cytoplasm was taken for reverse transcription (RT)-PCR as described by Eriksson et al (2001). Protocols of the RT reaction and PCR amplification were similar to those described previously (Vorobjev et al, 2000). A two-round amplification strategy was used in each protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Primers for the first amplification of calbindin (CB) and neuropeptide Y (NPY) were described by Cauli et al (1997); for the 2 d amplification, the same lower primers were used in combination with CB (sense2, TCCTGCTGCTCTTTCGATGC; size of product was 303 bp) or NPY (sense2, GCTCGTGTGTTTGGGCATTCT; 251 bp). The identity of cDNA sequences was revealed by sequencing the second-round amplification products, performed as described by Vorobjev et al (2000). The thin-walled PCR tubes contained a mixture of first-strand cDNA template (1.1 l), 10ϫ PCR buffer (5 l), 10 pM each of sense and antisense primer, and 200 M each of dNTP, and 2.5 U of Taq polymerase.…”
Section: Methodsmentioning
confidence: 99%